Apathy is associated with parietal cortical-subcortical dysfunction in ALS. (December 2021) - Caga, Jashelle; Tu, Sicong; Dharmadasa, Thanuja; Tse, Nga Y.; Zoing, Margaret C.; Huynh, William; Mahoney, Colin; Ahmed, Rebekah M.; Kiernan, Matthew C.
Abstract: Apathy is the core behavioural feature of frontotemporal dysfunction in amyotrophic lateral sclerosis (ALS). Initiation and emotional manifestations of apathy significantly affect patients and carers, particularly in terms of quality of life. As such, the primary aim of the present study was to investigate the prevalence and neural correlates of initiation, and emotional subtypes of apathy in ALS. A total of 109 participants were recruited from a specialised, tertiary referral ALS/FTD clinic. Overall rates of apathy, including cognitive, initiation and emotion subtypes as assessed by the Dimensional Apathy Scale (DAS), were examined and correlated with brain volumes, including voxel-based morphometry on high resolution MRI. Clinically significant apathy ranged between 49% (patient-rated DAS) and 64% (carer-rated DAS), with the most common apathy subtypes being initiation (84–96%) and emotional (74–75%) apathy. The results of the two-way repeated measures ANOVA revealed significant differences across the DAS executive, emotional and initiation subscales ( p  = .0001). Multivariate analysis using a logistic regression model showed that only initiation; (odds ratio = 3.08, p  = .004) and emotional (odds ratio = 2.40, p  = .008) apathy were predictive of clinically significant apathy, controlling for education and depression. Increased initiation apathy correlated with reduced grey matter within bilateral superior frontal gyrus and increased emotional apathy correlated with reduced grey matter in prefrontal cortices and right anterior cingulate, previously implicated in apathy. Additional correlations were identified including the angular gyrus (or the temporo-parietal junction), important in reward valuation and subsequent goal-directed behaviour. Taken together, results from the present series highlight the frequency and multi-dimensionality of apathy in ALS. The pathophysiological mechanisms of apathy in ALS may be critically underpinned by neurodegeneration across a distributed brain network, with key roles in task initiation, emotion, reward processing and subsequent goal-directed behaviour.